KANDUNGAN GIZI DAN DAYA TERIMA MI BASAH DENGANPENAMBAHAN TEPUNG IKAN GABUS (Channastriatasp) danSARI DAUN PANDAN WANGI(PandamusamarylifoliusRoxb) - Arrahim ali Purnama; Zulhaida Lubis; Fitri Ardiani (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Availability, processing restrictiveness, and potential nutrients contained in snakehead fish flour (Channa striata) and color and aroma of pandan leaves extract (Pandamus amarylifolius Roxh) can be utilized to create wet noodle. The wet noodle is expected to help improving nutritional status of children under five years old, particularly in Rundeng Subdistrict in Subulussalam City. The aim of this study was to create nutritious wet noodle with the addition of snakehead fish flour and pandan leaves extract which can be accepted by toddlers to adult. This research was an experimental research which used completely randomized design with 3 treatments ofsnakehead fish flour additions, which was 0%, 10% and 20% of total dough weight and 20% of the extract of pandan leaves for each treatment. Panelist in this research was 30 students of Public Health Faculty in Sumatera Utara University. Acceptance data test was analyzed with Kruskal Wallis`s test with significant level 5%. Nutrient analysis did in Laboratory of Industrial Research and Standardization Agency Medan. The characterization result of wet noodle showed that nutrient contentsof 100 g dough which was protein 4,64%, 5,86%, 6,34%, energy 101,9 kcal,108,43 kcal, 112,93 kcal, and iron 0,81 mg, 1,51 mg, 0,838 mg.The result of acceptability test showed that percentage of panelist acceptance of color, odor, taste, and texture was highest at 10% which was 86,67%, 86,67%, 82,22%, and 91,11% respectively. The result from acceptance test showed that the addition of snakehead fish flour did not have influence (p>0,05) on color, odor, taste, and texture of wet noodles. Wet noodle, with or without the addition of snakehead fish flour as similar are preferred by panelist. These noodles have little of energy, fats, and carbohydrate, but have much protein and enough of iron, so they can be consumed by toddlers to adult, especially for people who want to decrease their weight body. Keyword : Acceptability, Nutrient Content, Wet Noodles,Snakehead Fish Flour, Pandan Leaves Extract.